Being Ethical in a Context with Limited Ethics Oversight: A Study on Flooding Risk Management by Local Governments in India - Subramanyam, Nidhi (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2018)
This case describes and reflects on ethical questions that we faced as we obtained permission to conduct research on local government policy implementation processes in India, which has no legal guidelines or REBs for ethical oversight of social science research. We focus on questions of voluntary consent and exposure to unintended risks, where, in this case, staff in local governments might feel coerced to participate based on the institutional permission to conduct research granted by their superiors.